Testing Of EMA And Stock Return Predictability In BRICS Stock Markets (Journal of Namibian Studies : History Politics Culture, 2022)
The aim of this study is to evaluate the performance of the exponential moving average (EMA) strategy within the BRICS stock markets from June 2012 to June 2022. We examined three specific EMA rules: EMA(5-20), EMA(5-50), and EMA(5-200) to assess their ability to generate returns. Our findings indicated that the results of the EMA-based strategy were statistically insignificant in most cases, with the exception of some instances in the South African stock market. Overall, the EMA-based active strategy did not outperform the buy-and-hold (B-H) strategy, as the alpha ratio and compound annual growth rate (CAGR) were negative during the study period, except for the Russian stock market.